Faktor-Faktor Internal terhadap Pencegahan Fraud di BUMDES dengan Variabel Moral Sensitivity sebagai Moderasi - Nugroho, Aditya; Fahmi, Muhammad; Astarani, Juanda (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2024)
This research aims to analyze the influence of HR competency, whistleblowing, compliance with financial reporting, and internal control systems on fraud prevention in village-owned enterprises (BUMDES) management in Sungai Raya District, with moral sensitivity as the moderating variable. The research method used primary data and secondary data obtained through questionnaires. A sample of 85 respondents was selected using simple random sampling. The research results show that HR competency has a significant influence on fraud prevention, while whistleblowing does not have positive influence. Financial reporting compliance has a strong and significant connection with fraud prevention, while the internal control system does not have a significant connection. Apart from that, moral sensitivity is unable to moderate the influence of HR competency, whistleblowing, compliance with financial reporting, and internal control systems on fraud prevention by village-owned enterprises (BUMDES) managers.